Free at last? civil rights in the USA 1918-1968 - Kerr, John A. (National 4 & 5 history, 2018)
Exam Board: SQA Level: National 5 Subject: History First Teaching: September 2017 First Exam: Summer 2018 The recent changes in assessment for National 5 History have been fully incorporated in this new edition, as have changes in subject content which affect some but not all areas of the course. New marking rules systems and mark allocations have been fully recognised, and much fuller help and guidance has been provided in the assessment sections at the end of each chapter. This book: - Presents comprehensive coverage of the main areas of mandatory content - Provides guidance on assignment writing and assessment procedures for exam practice - Explains newly-introduced concepts and words with glossary boxes throughout the text - Offers suggestions are offered for further topic exploration beyond the textbook